Cost-Effectiveness of Endovascular Stroke Therapy: A Patient Subgroup Analysis From a US Healthcare Perspective. Issue 11 (November 2016) - Kunz, Wolfgang G.; Hunink, M.G. Myriam; Sommer, Wieland H.; Beyer, Sebastian E.; Meinel, Felix G.; Dorn, Franziska; Wirth, Stefan; Reiser, Maximilian F.; Ertl-Wagner, Birgit; Thierfelder, Kolja M.
Abstract : Background and Purpose—: Endovascular therapy in addition to standard care (EVT+SC) has been demonstrated to be more effective than SC in acute ischemic large vessel occlusion stroke. Our aim was to determine the cost-effectiveness of EVT+SC depending on patients' initial National Institutes of Health Stroke Scale (NIHSS) score, time from symptom onset, Alberta Stroke Program Early CT Score (ASPECTS), and occlusion location. Methods—: A decision model based on Markov simulations estimated lifetime costs and quality-adjusted life years (QALYs) associated with both strategies applied in a US setting. Model input parameters were obtained from the literature, including recently pooled outcome data of 5 randomized controlled trials (ESCAPE [Endovascular Treatment for Small Core and Proximal Occlusion Ischemic Stroke], EXTEND-IA [Extending the Time for Thrombolysis in Emergency Neurological Deficits–Intra-Arterial], MR CLEAN [Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands], REVASCAT [Randomized Trial of Revascularization With Solitaire FR Device Versus Best Medical Therapy in the Treatment of Acute Stroke Due to Anterior Circulation Large Vessel Occlusion Presenting Within 8 Hours of Symptom Onset], and SWIFT PRIME [Solitaire With the Intention for Thrombectomy as Primary Endovascular Treatment]). Probabilistic sensitivity analysis was performed to estimate uncertainty of the model results. Net monetary benefits, incremental costs, incremental effectiveness, and incremental cost-effectiveness ratios were derived from the probabilistic sensitivity analysis. The willingness-to-pay was set to $50 000/QALY. Results—: Overall, EVT+SC was cost-effective compared with SC (incremental cost: $4938, incremental effectiveness: 1.59 QALYs, and incremental cost-effectiveness ratio: $3110/QALY) in 100% of simulations. In all patient subgroups, EVT+SC led to gained QALYs (range: 0.47–2.12), and mean incremental cost-effectiveness ratios were considered cost-effective. However, subgroups with ASPECTS ⩽5 or with M2 occlusions showed considerably higher incremental cost-effectiveness ratios ($14 273/QALY and $28 812/QALY, respectively) and only reached suboptimal acceptability in the probabilistic sensitivity analysis (75.5% and 59.4%, respectively). All other subgroups had acceptability rates of 90% to 100%. Conclusions—: EVT+SC is cost-effective in most subgroups. In patients with ASPECTS ⩽5 or with M2 occlusions, cost-effectiveness remains uncertain based on current data. Abstract : Supplemental Digital Content is available in the text.